O movimento pleno de sentido: o que verdadeiramente faz sentido? um olhar para as aulas de educação física na perspectiva da pedagogia Waldorf - Gabriela Hilarino Simões (2023)
Physical Education within its specificities is an area of knowledge that brings important elements for human development. Based on the foundations presented by Rudolf Steiner in his anthroposophical theory, the research aims to present the possibilities of organizing the practice for the teaching of Physical Education, proposed in Steiner Schools, from the understanding of the movement with sense. To this end, it organizes a study of the author's works, assuming collaborative and narrative research as guiding axes of practical actions. In order to highlight the role of the teacher as a fundamental part for choosing the contents of the classes, the research had the participation of two Physical Education teachers and one elementary class teacher, with extensive experience in Waldorf Pedagogy, who present their memories, created in movement classes, with the students over the years. In the conversation circles, it was possible to verify that, although each teacher presents different experiences and activities, sometimes distinct, the basis that sustains the choices converges in the understanding they have about human development, always based on the principles of Anthroposophy. This movement of exchanging experiences served as a basis for making possible for the researcher and participating teachers to elaborate an Educational Resource entitled "Physical Education from the Waldorf perspective: broadening the look at other knowledges", presenting, through the experiences reported, what is important to be taken into account within the Waldorf pedagogy when thinking about Physical Education classes in elementary school, when a full development of the child is sought, that is, in the structuring of the body, in the balance of emotions and in the organization of ideas.